RETRACTED: Development of students’ data working competency in information technology lessons - Rashidov Anvarjon; Xalloqova Oygul (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001